2020
DOI: 10.21037/apm.2019.11.28
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin gallate reduces uric acid levels by regulating xanthine oxidase activity and uric acid excretion in vitro and in vivo

Abstract: Background: This study investigates the effect of epigallocatechin gallate (EGCG) from tea leaves on hyperuricemia and explores the underlying mechanisms in vitro and in vivo.Methods: The effects of EGCG on proliferation of BRL 3A rat liver cells were evaluated by CCK8 and after stimulation by xanthine the uric acid and xanthine oxidase (XOD) levels were evaluated by a kit; In an in vivo experiment, rats were treated with oxonic acid potassium salt combined with ethylamine pyrimidine to induce high uric acid h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 17 publications
1
25
0
Order By: Relevance
“…Also, this study reported that DGTP could reduce the concentration of uric acid in children, and in the adjusted model, the significant effect still existed. Some in vitro and in vivo studies ( 41 , 42 ) showed that GTP might have the effect of lowering uric acid through decreasing uric acid production and increasing uric acid excretion via the inhibition of xanthine oxidase activity and glucose transporter-9 expression and the promotion of organic anion transporter-1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Also, this study reported that DGTP could reduce the concentration of uric acid in children, and in the adjusted model, the significant effect still existed. Some in vitro and in vivo studies ( 41 , 42 ) showed that GTP might have the effect of lowering uric acid through decreasing uric acid production and increasing uric acid excretion via the inhibition of xanthine oxidase activity and glucose transporter-9 expression and the promotion of organic anion transporter-1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, green tea polyphenols dose-dependently decreased XO activity in the liver of the hyperuricemic mice. (13)(14)(15) It was also reported that the consumption of green tea inhibited the increase in plasma XO activity induced by exercise in weight-trained men. (23) In this study, U-Xa/Hx excretions were signi cantly higher in the SC group than in the SW group, indicating that the increase in U-Xa/Hx excretion in the SC group might be due to the effect of green tea catechins on XO activity, although we could not measure XO activity directly.…”
Section: Discussionmentioning
confidence: 92%
“…It has been reported that green tea polyphenols decrease serum UA concentrations by regulating XO activity and urinary excretion of UA in hyperuricemic mice. (13)(14)(15) In addition, green tea extract lowers serum UA concentrations in healthy individuals to some extent. (16) These studies together indicate a role for green tea catechins in UA metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…significantly reduced the renal expression of URAT1 and increased that of OAT1, thereby lowering the serum UA level and improving renal injury [ 147 ]. Epigallocatechin gallate exerted hypouricemic effects by suppressing XO activity and GLUT9 expression and promoting OAT1 expression in vivo and in vitro [ 148 ]. Tu-Teng-Cao extract remarkably decreased the concentration of serum UA in potassium oxonate-induced hyperuricemia rats [ 149 ].…”
Section: Perspective and Conclusionmentioning
confidence: 99%